205k views
1 vote
When given f(x)=3x+12, find f(f^-1(x))

1 Answer

6 votes

Answer:


\large\boxed{f\bigg(f^(-1)(x)\bigg)=x}

Explanation:


\text{Find}\ f^(-1)(x)


f(x)=3x+12\to y=3x+12

exchange x to y and vice versa:


x=3y+12

solve for y:


3y+12=x subtract 12 from both sides


3y=x-12 divide both sides by 3


y=(x-12)/(3)\to f^(-1)(x)=(x-12)/(3)


f\bigg(f^(-1)(x)\bigg)\to replace x in f(x) with the expression
(x-12)/(3)


f\bigg(f^(-1)(x)\bigg)=3\cdot(x-12)/(3)+12=x-12+12=x

User Alisia
by
5.6k points